2020
DOI: 10.1016/j.jcrs.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of posterior capsular rupture during phacoemulsification cataract surgery in eyes with previous intravitreal antivascular endothelial growth factor injections

Abstract: The Royal College of Ophthalmologists (RCOphth) is the professional body for eye doctors, who are medically qualified and have undergone or are undergoing specialist training in the treatment and management of eye disease, including surgery. As an independent charity, we pride ourselves on providing impartial and clinically based evidence, putting patient care and safety at the heart of everything we do. Ophthalmologists are at the forefront of eye health services because of their extensive training and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
6
17
2
Order By: Relevance
“…The prevalence of PCR observed in our patients with a history of intravitreal anti-VEGF therapy was 7.45% (95% CI: 5.9–9.32%). Despite this value representing the pooled prevalence from surgeons with various levels of experience, it is remarkable because it is significantly higher than that found in previous reports [ 9 11 ]. The reason for such an increase is unknown.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…The prevalence of PCR observed in our patients with a history of intravitreal anti-VEGF therapy was 7.45% (95% CI: 5.9–9.32%). Despite this value representing the pooled prevalence from surgeons with various levels of experience, it is remarkable because it is significantly higher than that found in previous reports [ 9 11 ]. The reason for such an increase is unknown.…”
Section: Discussioncontrasting
confidence: 69%
“…These authors successfully identified through multiple logistic regression models that the experience of the cataract surgeon (OR: 1.83–2.83), cataract progression grade (OR: 2.67–2.84), number of previous intravitreal injections (>10, OR: 2.59), and male sex (OR: 1.49) were potential associated risk factors for PCR [ 9 , 10 ]. Finally, in early 2020, another group identified a dose-dependent increase of 8.6% (OR: 1.086, 95% CI: 1.04–1.135, p < 0.01) in relative risk per injection, especially in those receiving more than 10 injections [ 11 ]. Eventhough the evidence is compelling, there are some contradictions among the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis considering intravitreal injections as a categorical variable identified 10 or more previous injections that were associated with a 2.6 times greater likelihood of PCR (p = 0.003) after adjusting for other significant independent predictors. Three independent studies have supported this observation, one from the USA, and two others from the UK [47][48][49]. Much like we see with COVID-19 vaccine development, rare adverse events can be identified outside of a clinical trial setting in real-world settings [50].…”
Section: Managing Posterior Capsular Rupture or Zonular Dialysis During Cataract Surgerymentioning
confidence: 78%